Regional Variation in the Mechanical and Microstructural Properties of the Human Anterior Cruciate Ligament. (November 2016) - Skelley, Nathan W.; Castile, Ryan M.; Cannon, Paul C.; Weber, Christian I.; Brophy, Robert H.; Lake, Spencer P.
Background: The anteromedial (AM) bundle of the anterior cruciate ligament (ACL) has a higher modulus and failure stress than does the posterolateral (PL) bundle. However, it is unknown how these properties vary within each bundle. Purpose: To quantify mechanical and microstructural properties of samples within ACL bundles to elucidate any regional variation across the ligament. We hypothesized that there are no differences within each bundle in contrast to cross-bundle variation. Study Design: Descriptive laboratory study. Methods: Sixteen human ACLs were dissected into AM and PL bundles. Three samples were taken from each bundle in an ordered sequence from AM (region 1 AM bundle) to PL (region 6 PL bundle). Each sample was tested in uniaxial tension, using quantitative polarized light imaging (QPLI) to quantify collagen fiber alignment. After preconditioning, samples were subjected to a stress-relaxation (SR) test followed by quasistatic ramp-to-failure (RF). Peak and equilibrium stress values were computed from the SR test and modulus quantified in the toe- and linear-regions of the RF. QPLI values describing collagen orientation (angle of polarization [AoP]) and strength of alignment (degree of linear polarization [DoLP]) were computed for the SR test and at points corresponding to the zero, transition point, and linear region of the RF. Results: Toe- and linear-region modulus values decreased from region 1 to 6. Slopes of regression lines increased for the average DoLP during RF, with significance at higher strains. The standard deviation of AoP values decreased during RF, indicating tighter distribution of orientation angles, with significant correlations at all points of the RF. During SR, stress values uniformly decreased but did not show significant linear regression by region. DoLP and AoP values changed slightly during SR and demonstrated significant linear variation by region at both peak and equilibrium points. Conclusion: Most microstructural and material properties evaluated in this study appear to follow a linear gradient across the ACL, rather than varying by bundle. Clinical Relevance: This AM-to-PL variation provides a more accurate description of functional tissue anatomy and can be used to assess and guide techniques of ACL reconstruction.